Revisiting HRCT Features of ABPA - Debi, Uma; Maralakunte, Muniraju; Singh, Lokesh; Garg, Mandeep Kumar; Bhatia, Vikas; Devi, Gita; Sinha, Anindita (Archives of Clinical and Medical Case Reports, 2020)
Allergic bronchopulmonary aspergillosis (ABPA) is an abnormal immune response (hyper-sensitivity) mounted against Aspergillus fumigatus in predisposed immunocompetent hosts. This entity is commonly seen in individuals with bronchial asthma and rarely in cystic fibrosis. Serological and radiological tests help to confirm the diagnosis. High resolution computed tomography (HRCT) is the radiological modality of choice for investigating ABPA subjects. The subjects with ABPA may present variably with no HRCT abnormalities, bronchiectasis, high attenuation mucus (HAM) and chronic fibrotic lung changes. The presence of HAM represents immunological severity and also indicates higher chances of relapse. HAM is pathognomonic for ABPA. HRCT findings of ABPA are reviewed in this article.